Polymorphism of Growth Hormone Gene in Selecting Etawah Crossbred (PE) Goats - Tri Eko Susilorini; Kuswati Kuswati; Sucik Maylinda (Research Journal of Life Science, 2017)
Although Etawah Crossbred (PE) goat is considered to be dual purpose (meat and milk) goat, it is mainly raised for meat production. Since early 1990, there has been a growing interest of the farmer in some places to raise PE goat for milk production without sacrificing its role to produce kids for meat. Although milk yield of PE goat was not as high as milk yield of some other dairy goats, the ability of PE goat to cope with harsh local environment, particularly climate and feed conditions, was an advantage. Therefore, raising PE goat would still be an important part of farmer activities in the rural areas in Indonesia. Identification of the genes underlying livestock production traits leads to more efficient breeding programs and it is a promising way to improve production traits of farm animals. Growth hormone is a polypeptide hormone which is the major regulator of the metabolic procedures of growth and development and it is encoded by GH gene. The objective of this study was to detect the genetic polymorphism of GH gene in major Etawah Crossbred (PE) goat using PCR-RFLP. The PCR amplified fragment were digested with HaeIII endonuclease and the result showed the presence of two genotype CC and CD. The total frequency were 47.0% and 53.0% for CC and CD genotype respectively in 94 tested goats. Statistical analysis showed that in the fragment amplified by the pair of  primer, CD genotype had significant higher birth weight and weight of 100 days old (weaning weight) than CC genotype (P<0.01). In conclusion that GH gene may be a mayor gene or linked to the mayor gene to affect the weight traits and the polymorphic site could be used to select the goat weight in marker-assisted selection program.